Training program to support posbindu cadre knowledge and community health centre staff in the Geriatric Nutrition Service - Fatmah, Fatmah (ASEAN Journal of Community Engagement, 2020)
The geriatric minimal service standard (SPM) coverage in Depok has steadily decreased from 37.53% in 2013 to 11.8% in 2018. One factor affecting the problem is a lack of patient participation and the inability of posbindu (integrated service post for older people) cadres to perform their tasks. To increase the coverage of older people visiting posbindu, it is necessary to raise the knowledge and skill levels of posbindu cadres and community health centre staff in Depok. The skills include performing nutritional status assessment (NSA) and screening, early detection of dementia, independence assessment, and elderly nutrition counselling. This is a case-based article focusing on geriatric nutrition training for posbindu cadres and community health service staffs. We undertook training for 35 subjects (22 posbindu cadres and 13 community health centre staff). At the end of the training, the mean score of the elderly nutrition knowledge had increased to 52.5 points. The score before training significantly differed with post-training (p = 0.001). The knowledge of subjects who have the previous training was also significantly different from those who did not have the previous training (p = 0.017). The knowledge of posbindu cadres and community health centre staffs can be improved through elderly nutrition training. Technical assistance and monitoring performed three months after the training measured their ability to perform the geriatric nutrition services. They should be able to demonstrate how to educate older people in the diabetes mellitus nutrition campaign, metabolic syndrome, nutrition-balanced diet, and gout; also, how to conduct predicted height measurements using the knee-height predictor, and how to fill MNA, MMSE, BADL, and IADL instruments. We suggest the geriatric nutrition training program will increase SPM coverage at Depok City.